Conservation status and natural history of Ctenomys, tuco-tucos in Bolivia - Gardner, Scott Lyell; Botero-Cañola, Sebastian; Aliaga- Rossel, Enzo; Tsogtsaikhan Dursahinhan, Altangerel; Salazar-Bravo, Jorge (Therya, 2021)
Abstract The genus Ctenomys consists of about 70 species and in addition to the Geomyidae of the Nearctic, Neotropical tuco-tucos represent a well-documented case of diversification in the subterranean biotype. Here we will: i) Provide an updated summary of the natural history of the 12 species of extant tuco-tucos from Bolivia; ii) Update information on distributions of each species; and iii) Using ecological niche modeling, evaluate recent and projected habitat transformation or habitat degradation within the known range of each species to provide a preliminary assessment of the preservation or conservation status of ctenomyids within Bolivia. We follow Gardner et al. (2014) and combine species summaries with both updated published and new data to compile a complete list of known extant species of tuco-tucos from Bolivia. Occurrence data for Ctenomys in Bolivia and surrounding areas were extracted from the database Arctos and GBIF. All individual specimen-based locality records were checked and georeferenced by referring to original museum collection records. We created species distribution models for the species with enough locality records using climate and soil data, while for the rest of the species we estimated the ranges based on the known occurrence localities. Finally, we quantified the amount of large-scale habitat conversion occurring within each species range, as well as the potential effect of climatic change on species distribution. Here we present information regarding the biology of tuco-tuco (Ctenomys) species known to occur in Bolivia, including unpublished natural history data such as habitat association, interactions and activity patterns gathered by the authors through extensive field work. Besides this, we estimated the current distribution of Ctenomys species, quantified large-scale habitat transformation within each species range and assessed the potential effect of climatic change on five tuco-tuco species. We found that the habitats within the ranges of C. boliviensis and C. steinbachi have experienced significant land-cover conversions in recent years. We also show that C. opimus, as well as the above mentioned species are expected to undergo range contractions resulting from climatic change by 2070. Our review shows that there is a dearth of information regarding natural history, taxonomy and distribution for many Bolivian tuco-tuco species. Nonetheless, the information presented here can be a tool for directing and focusing field studies of these species. This is of great importance if we take into account that most of the Bolivian tuco-tucos are subject to one or several conservation/preservation threats. These include: Habitat destruction via land use or climatic changes in conjunction with geographic ranges of Ctenomys that are small in areal extent and which in many cases are not adequately covered by protected areas.